2018
DOI: 10.1038/s41598-018-29137-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum RUVBL3 protein: a novel DNA modifying enzyme and an interacting partner of essential HAT protein MYST

Abstract: RUVBLs constitute a conserved group of ATPase proteins that play significant role in a variety of cellular processes including transcriptional regulation, cell cycle and DNA damage repair. Three RUVBL homologues, namely, PfRUVBL1, PfRUVBL2 and PfRUVBL3 have been identified in P. falciparum, unlike its eukaryotic counterparts, which have two RUVBL proteins (RUVBL1 & RUVBL2). The present study expands our understanding of PfRUVBL3 protein and thereby basic biology of Plasmodium in general. Here, we have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…For routine culture, haematocrit was maintained at 5% and the stages and growth of parasite was routinely monitored by microscopic examination of Giemsa-stained blood smears. Synchronization of parasite culture was done using 5% sorbitol method as discussed elsewhere [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…For routine culture, haematocrit was maintained at 5% and the stages and growth of parasite was routinely monitored by microscopic examination of Giemsa-stained blood smears. Synchronization of parasite culture was done using 5% sorbitol method as discussed elsewhere [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 0 0 9 ) : P F 3 D 7 _ 0 8 0 9 7 0 0 ( P f R U V B L 1 ) , PF3D7_1106000 (PfRUVBL2), and PF3D7_1362200 (PfRUVBL3). Sequence analysis has shown that PfRUVBL1 and PfRUVBL2 proteins are closer to yeast and human Rvb1/RUVBL1, whereas PfRUVBL3 is closer to Rvb2/RUVBL2 (Ahmad et al 2012(Ahmad et al , 2013Tuteja 2013a, 2013b;Sen et al 2018). The similarity between PfRUVBL3 and yeast Rvb2 has been demonstrated, since it was able to complement Rvb2 functions in yeast (Sen et al 2018).…”
Section: R2tp In Plasmodium Falciparummentioning
confidence: 97%
“…Sequence analysis has shown that PfRUVBL1 and PfRUVBL2 proteins are closer to yeast and human Rvb1/RUVBL1, whereas PfRUVBL3 is closer to Rvb2/RUVBL2 (Ahmad et al 2012(Ahmad et al , 2013Tuteja 2013a, 2013b;Sen et al 2018). The similarity between PfRUVBL3 and yeast Rvb2 has been demonstrated, since it was able to complement Rvb2 functions in yeast (Sen et al 2018). Interestingly, PfRUVBL1 has a longer N-terminal region in comparison with its human and yeast orthologues, yet its functional role is unknown (Ahmad and Tuteja 2013a).…”
Section: R2tp In Plasmodium Falciparummentioning
confidence: 99%
See 2 more Smart Citations